PENGARUH LATIHAN EL-RONDO TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAK BOLA - Hillmy, Fachrul; Mochamad Zakky Mubarok; Nur Mahfuzah Agustin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of el-rondo training on passing skills in football. The research method used is the experimental method. The research design is a pre-experimental design with a one-group pretest-posttest design. The participants in this study consisted of 20 SSB PSPS Segeran players aged 13-14 years. The sampling technique used was saturated sampling. The research instrument used was the passing skill instrument from Rogalski and Degel. The results revealed that el-rondo training had a significant effect on passing skills in football.